Monarchic Spaces in Quatrevingt-treize by Victor Hugo - Costa Ribeiro, Rosária Cristina (Íkala, Revista de Lenguaje y Cultura, 2008)
This article presents the obtained results throughout the Master degree dissertation, entitled The role of spatiality in Quatrevingt-treize (1814) by Victor Hugo, in which it is analyzed how The French Revolution redefined some meanings and contributed to the formation of the contemporary world. In this traditional historical novel, the literary composition of rebellious and monarchic spaces is observed by means of a romantic and turn-of-the-century vision. During the reading of the book, we are surprised by a narration expressing resistance to the revolutionary progress in 1793: ’the War of Vendéia’, an eminently monarchist and feudal space, in opposition to that of revolutionary Paris. Recibido: 30-03-2008 / Aceptado: 21-07-2008 How to reference this article: Costa Ribeiro, R. C. (2008). Caracterização dos espaços monárquicos em Quatrevingt-treize de Victor Hugo. Íkala. 13(2), pp.185-205